The Effect of Work Discipline and Work Environment on Employee Performance with Organizational Culture as a Mediating Variable at Syntax Corporation Indonesia - Upit Elya Rohimi; Edy Hartono; Kartono Kartono (International Journal Labs, 2026)
This research eximines how work discipline and environment influence employee performance, while considering organizational culture being a mediating factor at Syntax Corporation Indonesia. Employee performance is a crucial element to achieving organizational goals, but factors such as work discipline and environment exert an influential impact on this issue. This study uses a quantitative and surveyed 192 employees via saturated sampling and analyzed the data utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM). The outcomes unfolded that work discipline own a positive significant and influential effect to employee performance which the coefficient that is 0.229 and the p-value that is < 0.05. The work environment similarly bring a meaningful positive effect to employee performance alongside the coefficient is 0.285 and the p-value < 0.05. In addition, organizational culture was identified as a mediating variable that enhances the effect from both work discipline and the work environment to employee performance, with mediation effects that is 0.167 and 0.155, respectively. The mediation was determined to be partial, suggesting that while organizational culture strengthens these relationships, other factors may also contribute. These findings provide notable perceptions for human resource management on the Indonesian context, highlighting that employee performance could be improved by cultivating disciplined work practices, a supportive environment, and a strong organizational culture.